2018
DOI: 10.1002/2017jb015386
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on North Anatolian Fault Zone Width in the Crust and Upper Mantle From S Wave Teleseismic Tomography

Abstract: We present high‐resolution S wave teleseismic tomography images of the western segment of the North Anatolian Fault Zone (NAFZ) in Turkey using teleseismic data recorded during the deployment period of the Dense Array for Northern Anatolia array. The array comprised 66 stations with a nominal station spacing of 7 km, thus permitting a horizontal and vertical resolution of approximately 15 km. We use the current S wave results with previously published P wave teleseismic tomography to produce maps of relative V… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 69 publications
(133 reference statements)
3
20
0
Order By: Relevance
“…A number of teleseismic studies have measured variations in V P /V S by jointly inverting P and S arrival time data sets (e.g., Hammond & Humphreys, 2000;Schmandt & Humphreys, 2010a). A recent work by Papaleo et al (2018) estimated V P /V S from teleseismic data that constrain relative rather than absolute velocities; for this approach to be successful, accurate estimates of the background P wave and S wave velocity structure are required. However, both P wave and S wave velocity models are often not available for the same region and when they are, limitations arising from the resolving power of the tomography contaminate R S,P estimates (e.g., Deschamps & Trampert, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A number of teleseismic studies have measured variations in V P /V S by jointly inverting P and S arrival time data sets (e.g., Hammond & Humphreys, 2000;Schmandt & Humphreys, 2010a). A recent work by Papaleo et al (2018) estimated V P /V S from teleseismic data that constrain relative rather than absolute velocities; for this approach to be successful, accurate estimates of the background P wave and S wave velocity structure are required. However, both P wave and S wave velocity models are often not available for the same region and when they are, limitations arising from the resolving power of the tomography contaminate R S,P estimates (e.g., Deschamps & Trampert, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Low Pwave velocities observed by Papaleo et al (2017) are also colocated with the low S-wave velocities detected in this study beneath the Pamukova basin. Papaleo et al (2017Papaleo et al ( , 2018 also found relatively high seismic velocity at depth within the Armutlu Block. We detect high S-wave velocities much closer to the surface that we attribute to the shallow metamorphic rocks reported in this region (Yılmaz et al, 1995).…”
Section: S-wave Velocity Modelmentioning
confidence: 88%
“…Seismic velocity models of the crust in this region have also been constructed from teleseismic body wave tomography by Papaleo et al (2017Papaleo et al ( , 2018. They image depthaveraged seismic velocity between the surface and 90 km of depth, with a vertical and horizontal resolution of ∼ 15 km (Papaleo et al, 2017(Papaleo et al, , 2018.…”
Section: S-wave Velocity Modelmentioning
confidence: 99%
See 2 more Smart Citations